New Frontiers in Enterprise Risk Management - Olson, David L.; Wu, Desheng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2008)
This book provides introductory material about enterprise risk management, and the role of risk in decision making. It presents enterprise risk management from perspectives of finance, accounting, insurance, supply chain operations, and project management. Technology tools are addressed, to include financial models of risk as well as accounting aspects using data envelopment analysis, neural network tools for credit risk evaluation, and real option analysis applied to information technology outsourcing. Three chapters present enterprise risk management experience in China, to include banking, chemical plant operations, and information technology. .
Preliminary -- The Human Reaction to Risk and Opportunity -- ERM Perspectives -- Enterprise Risk Management: Financial and Accounting Perspectives -- An Empirical Study on Enterprise Risk Management in Insurance -- Supply Chain Risk Management -- Two Polar Concept of Project Risk Management -- ERM Technologies -- The Mathematics of Risk Transfer -- Stable Models in Risk Management -- Hybrid Calibration Procedures for Term Structure Models -- The Sarbanes-Oxley Act and the Production Efficiency of Public Accounting Firms -- Credit Risk Evaluation Using Neural Networks -- Applying the Real Option Approach to Vendor Selection in IT Outsourcing -- Applications of ERM in China -- Assessment of Banking Operational Risk -- Case Study of Risks in Cailing Chemical Corporation -- Information Technology Outsourcing Risk: Trends in China.
Keywords: Finance; Accounting; Bookkeeping .; Information technology; Business—Data processing; Finance, general; Accounting/Auditing.; IT in Business